Guest editorial - Lanitis, Andreas; Tsapatsoulis, Nicolas (My University, 2017)
This Special Issue includes extended and updated versions of selected papers presented at the 4th International Workshop on Biometrics and Forensics (IWBF), held in Limassol, Cyprus during March 2016. IWBF is an annual workshop initiated by the European COST Action IC1106 ‘Integrating Biometrics and Forensics for the Digital Age’. IWBF provides a meeting place for those concerned with the usage of biometric recognition systems in forensic science applications, attracting participants from academia, industry, law enforcement agencies, and user communities. This Special Issue contains nine papers that span three thematic areas: Biometric Sensors and Data Enhancement, Voice and Multi-Modal Biometrics, and Behavioural Biometrics.
Keywords: Biometric sensors; Data Enhancement